An investigation of executive functioning, attention and working memory in compulsive hoarding - McMillan, S.; Rees, Clare; Pestell, C. (2013)
Background: Compulsive Hoarding involves the acquisition of, and failure to discard, a large number of possessions that appear to be useless or of limited value, cluttered living spaces and significant distress or impairment in functioning (Frost and Hartl, 1996). The problem is multifaceted and appears best explained by a cognitive-behavioural framework. Aims: This study set out to test one aspect of Frost and Hartl's (1996) cognitive-behavioural model of compulsive hoarding by investigating theorized cognitive deficits in executive functioning, such as working memory and attention. Method: 24 participants with compulsive hoarding were tested on the Digit Span, Spatial Span and the Wisconsin Card Sorting Tests (WCST). Results: On the WCST, the hoarding group had a significantly higher number of perseveration errors (t = 1.67, p = .005) and significantly lower numbers of categories completed (t = −2.47, p = .001) than test norms. Only “failure to maintain set” was significantly correlated with hoarding severity (r = .435, p < .05). Conclusions: These findings lend support to the theory that people who compulsively hoard have executive dysfunction, which impacts on their ability to process information. Deficits relate to difficulties in forming effective strategies, inadequate feedback response, problems in concept formation, and impulsivity. Difficulties in sustained attention also appeared to be a factor in hoarding severity. These findings are important in directing more targeted clinical interventions.